2002
DOI: 10.1038/nri915
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory lipid mediators and insights into the resolution of inflammation

Abstract: The pro-inflammatory signalling pathways and cellular mechanisms that initiate the inflammatory response have become increasingly well characterized. However, little is known about the mediators and mechanisms that switch off inflammation. Recent data indicate that the resolution of inflammation is an active process controlled by endogenous mediators that suppress pro-inflammatory gene expression and cell trafficking, as well as induce inflammatory-cell apoptosis and phagocytosis, which are crucial determinant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
543
0
32

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 774 publications
(590 citation statements)
references
References 61 publications
8
543
0
32
Order By: Relevance
“…Multiple functions, dependent on concentration, location and timing have been described for the prostaglandins (e.g.PGD 2 and PGE 2 ) [1-3,24,25]. In order to examine the immunological responses triggered by the 603600∆/∆, 800020∆/∆ and 807710∆/∆ , we stimulated human PBMC-DMs for 24 hours with each strain and determined the amount of cytokine and chemokine production.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Multiple functions, dependent on concentration, location and timing have been described for the prostaglandins (e.g.PGD 2 and PGE 2 ) [1-3,24,25]. In order to examine the immunological responses triggered by the 603600∆/∆, 800020∆/∆ and 807710∆/∆ , we stimulated human PBMC-DMs for 24 hours with each strain and determined the amount of cytokine and chemokine production.…”
Section: Resultsmentioning
confidence: 99%
“…During vasodilation prostaglandins and leukotrienes induce increased permeability of post capillary venules and also recruit complement components and leukocytes to the site of inflammation [2]. In contrast, lipoxins act as pro-resolving lipid mediators, as for example, LXA 4 inhibits the recruitment of neutrophil and eosinophil granulocytes in post capillary venules [3]. Previously, it has been hypothesized that, during fungal infection the invading fungi induce host prostaglandin biosynthesis that causes a local anti-inflammatory response, which in turn could contribute to fungal invasion [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro studies have shown that repetitive mechanical loading of tendon fibroblasts induces the release of PGE 2 and LTB 4 (Almekinders et al, 1995;Li et al, 2004). Both are also produced in substantial amounts at the sites of inflammation (Henderson, 1994;Lawrence et al, 2002). PGE 2 and LTB 4 are inflammatory mediators and have been implicated in the pathogenesis of several inflammatory diseases such as tendinopathy and rheumatoid arthritis (Davidson et al, 1983;Almekinders et al, 1993;Trebino et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies indicated that inflammation resolution depends greatly on the expression of specific cytokines [42][43][44] such as interleukin (IL)-10 and transforming growth factor-β (TGF-β), and lipid mediators such as lipoxins [43], protectins, and resolvins [45][46][47]. Moreover, self-limited inflammation resolution following acute inflammation is a coordinated event initiated by an active "class switch" from prostaglandins and leukotrienes inflammatory mediators to resolvins, lipoxins, protectins, and maresins through complex processes involving multiple enzymes and cell types [48].…”
Section: Inflammation Resolution Mediatorsmentioning
confidence: 99%